Electric conductivity levels in irrigation water and application of biofertilizer in peanut Br1 crops - Alves, Lunara de Sousa; Véras, Mário Leno Martins; Araújo, Danila Lima de; Melo Filho, José Sebastião de; Irineu, Toni Halan da Silva; Andrade, Raimundo (Comunicata Scientiae, 2018)
Peanut is an oilseed cultivated in semiarid region. However, the lack of knowledge about irrigation and fertilization makes it difficult to increase its yield. Thus, the aim of this research was to study the effect of irrigation with water of different electrical conductivities and application of biofertilizer in peanut Br1. The research was carried out from August to November, 2014 at the State University of Paraíba - Campus IV, Brazil. The study was performed in a completely randomized design in a 4x2 factorial scheme, with four replicates. The treatments were related to different electrical conductivities in the irrigation water: (S1 = 0.8; S2 = 1.5; S3 = 3; e S4 = 4.5 dS m-1) with and without biofertilizer application. It was verified that the electrical conductivity influenced significantly all analyzed variables, except root fresh mass. For biofertilizer application, according to the Tukey´s test, only plant height and number of leaves were significantly influenced. Electrical conductivities in irrigation water above 0.8 dS m-1 reduce peanut growth and biomass production. The application of biofertilizer provides positive results in peanut cultivation in a Fluvic Neosol.